STIMULASI KECERDASAN MAJEMUK ANAK USIA DINI DENGAN BERMAIN SELOP TERBANG - Rahmayeni Simajuntak; Ririn Suryani; Novia Saputri; Nurartina Marpaung; Supia (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2023)
The purpose of this research is expected to be able to improve the quality of learning at Ra Bunda Isnaini Mawardi in order to achieve a quality education system, especially for stimulating children's multiple intelligences. The research method is an experimental method with intelligence stimulation research objects and research subjects, namely children at Ra Bunda Isnaini Mawardi, and with data collection techniques such as discussions, observations. The results of this study indicate that the multiple intelligences of early childhood at Ra Bunda Isnaini Mawardi are almost perfect with success criteria.